Estimation of Soil C-Organic Content Based on Reflectance Values Generated from Spectrometer - Salmia, Salmia; Useng, Daniel; Samsuar, Samsuar (Salaga Journal, 2025)
C-Organic is an important component of soil fertility. The intensity of agricultural land use affects the organic matter content in the soil. A spectrometer can be used to measure organic matter content through reflectance values. This study aimed to compare reflectance values and C-Organic content in rice fields with planting Index (IP) of 100 and IP of 300 in Maros Regency, as well as to analyze the relationship between reflectance values and laboratory test results. The method used involved collecting soil samples from both types of rice fields, measuring reflectance using a spectrometer in the Blue, Green, Red, and NIR spectra, and analyzing their relationship with C-Organic content. The results showed that reflectance values and C-Organic content in 300 IP were higher than in 100 IP, with the highest coefficient of determination (R²) was in red spectrum, i.e. 0.9425. The C-Organic content at the research field was classified as very low, ranging from 0.61 to 1.05%, with a higher average in 300 IP (0.96%) compared to 100 IP (0.74%). This study concluded that a spectrometer can be a fast and accurate alternative for detecting soil C-Organic content, especially at a wavelength of 650 nm.